(Pyrazolylethyl-amine)zinc(II) carboxylate complexes as catalysts for the copolymerization of CO2 and cyclohexene oxide. (1st November 2020) - Matiwane, Anelisa; Obuah, Collins; Darkwa, James
Graphical abstract: This manuscript describe the synthesis and characterization of (Pyrazolylethyl-amine)zinc(II) carboxylate complexes and their use as catalysts for the copolymerization of cyclohexane oxide and carbon dioxide. The polymers produced was 98% selective toward poly(cyclohexene carbonate) at an optimum temperature of 100 °C and pressure of 4.5 MPa for 24h. Highlights: Synthesis (Pyrazolylethyl-amine)zinc(II) carboxylate complexes. Characterization by NMR, FTIR, mass spectrometry and crystal X-ray diffraction. These complexes were used to convert epoxides and CO2 to poly carbonates. Abstract: Pyrazolyl compounds 2-(3, 5-di- tert -butyl-1H-pyrazol-1-yl)ethyl-amine) (L1 ), 2-(3, 5-diphenyl-1H-pyrazol-1-yl)ethyl-amine (L2 ), and 2-(3-phenyl-5-(trifluoromethyl)-1H-pyrazol-1-yl)ethyl-amine (L3 ) were reacted with a mixture of zinc(II) acetate and 3, 5-dinitrobenzoic acid to form the bidentate complexes [(2-(3, 5-di- tert -butyl-1H-pyrazol-1-yl)-ethyl-amine)-Zn(C6 H5 COO(NO2 )2 ] (1 ), [(2-(3, 5-diphenyl-1H-pyrazol-1-yl)ethyl-amine)Zn(C6 H5 COO(NO2 )2 ] (2 ), and [(2-(5-phenyl-3-(trifluoro-methyl)-1H-pyrazol-1-yl)ethyl-amine)Zn(C6 H5 COO(NO2 )2 ] (3 ) respectively. All three zinc complexes were tested as catalysts for the copolymerization of CO2 and cyclohexene oxide (CHO) and found active to form poly(cyclohexene carbonate) (PCHC) and cyclohexene carbonate (CCHC) at CO2 pressures as low as 1.5 MPa and under solvent-free conditions in the absence of a co-catalyst. Increase in CO2 pressure resulted in activity and showed selectivity up to 99% selectivity for the formation of the copolymer PCHC. Optimum temperature for the polymerization was 100 °C and even at this temperature selectivity towards formation of PCHC was found to be 99%. The copolymers obtained have moderate molecular weights (3860–11, 500 g/mol) and polydispersity indices varying from 2.73 to 4.93.